"Knowledge, Attitudes, and Practices on Water, Sanitation, and Hygiene among Tea Garden Workers in Sylhet: A Cross-Sectional Study" (Bangladesh Journal of Medical Education, 2025)
Background and objective: Tea Garden workers, often living in remote and underdeveloped areas, face inadequate sanitation facilities and lack access to clean water. This research aims to gather baseline data on tea garden workers' sanitation and hygiene knowledge, attitudes, and practices in Sylhet, Bangladesh. Methods: A cross-sectional study was undertaken among 380 respondents in the Moulvibazar districts of Sylhet division from January 2022 to December 2022. A convenient sampling technique was applied. The study employed a pretested, semi-structured questionnaire to gather information on sociodemographic traits and current attitudes, behaviors, and knowledge related to sanitation and hygiene. Software called SPSS 25.0 was used to analyse the data. Results: A majority (76%) of respondents demonstrated hand hygiene awareness, with 56% recognizing the importance of clean water. Most participants (90%) believed that water quality impacts health and 91% associated unsafe drinking water with gastrointestinal issues. Further, 78% agreed on the necessity of water treatment for safety. Awareness of handwashing before handling food was high (90%). For waste management, 67% utilized community dustbins, while 81% emphasized home cleanliness as part of sanitation, though only 15% noted proper waste disposal as essential. Indicators of poor sanitation, like visible garbage, were recognized by 83% of the workers. Sanitation knowledge was found to be strongly correlated with both family size (p = 0.0002) and socioeconomic position (p = 0.03). Hygiene practices were also significantly related to gender (p = 0.004), socio-economic status (p = 0.008), and family size (p = 0.0001). Interpretation and conclusion: These findings indicate that while general awareness and practices are high, socio-economic and demographic factors play crucial roles in shaping specific sanitation behaviors and knowledge.BJME, Volume-16, Issue-02, July 2025: 67-77